RELATIONAL SPACE: The Digital Interactive Art Space at Vallensbaek Train Station - Jakobsen, Annette Svaneklink (2018)
DIAS, the Digital Interactive Art Space, is the first curated exhibition space in Denmark to focus solely on the digital art field. Since its opening in 2014, DIAS exhibits works by Danish and international artists with practices based on digital and electronic media, for example, video art, sound art and interactive artworks. DIAS is situated in the fully functioning Vallensbaek station southwest of Copenhagen. While merging with the daily rhythms of its host, the art space is open to the public around-the-clock. Based on experiences, photographs, and an interview with the daily leader of DIAS, this article investigates how understandings of intensity and relation based on works by Gilles Deleuze and Sylvia Lavin can provide knowledge about how digital art can be a potential resource in our everyday surroundings, and how Vallensbaek station exhibits digital and interactive art for it to become a potential resource in the train passengers' lives.